Cultural Globalization and its Educational Effects on the Arab World and Ways of Facing them – A theoretical analytic study – - Nsairat, Mahmoud Saleh (Journal of Educational and Psychological Sciences, 2020)
The objective of this study was to investigate the educational effects of cultural globalization on the Arab world and ways to face them. The study adopted the deductive analytic method. The results showed that globalization is a state we live in different spheres of life, and manifestations of cultural globalization in its impact on the Arab cultural identity. It is considered as a cultural invasion unilaterally violated the privacy of Arab society and its principles. The English language became the first globally in terms of teaching in universities and widely used in most areas of life. The impact of cultural globalization seriously spread by the media, which is one of the pillars of cultural globalization on access to members of the community and influence them. The effects of educational cultural globalization in the Arab world is represented in the prevalence of consumer culture, individualism, selfishness, alienation, isolation from human society, the culture of the prevalence of sex, violence, pornography, and unrestricted freedom. Finally, the results showed that cultural globalization can be faced through the introduction of achievements of globalization and take advantage of them in the scientific and technological side, as well as the emphasis on the Arab cultural identity, instills the values ​​of loyalty and belonging to the Arab community. Many recommendations were presented such as offering the best efforts to benefit from the advantages of the cultural organization, adopting the technological and scientific choices and employing them in all fields and keep pace with the global technological and scientific revolution to give the Arab world its distinguished status among the countries of the world.
Keywords: cultural globalization; cultural invasion; cultural identity; consumption culture